Traditional Chinese medicine paraffin therapy: an evidence-based overview from a modern medicine perspective - Wenxi Yan; Lanping Liu; Tao Yang; Xiaochen Yang (BMC, 2022)
Abstract External therapy of traditional Chinese medicine and paraffin therapy are both traditional Chinese forms of treatment. In recent years, external use of traditional Chinese medicine combined with paraffin therapy, which involves combining meridians, acupoints, drugs, and hyperthermia, has demonstrated great effectiveness in treating certain conditions. An overview of traditional Chinese medicine paraffin therapy (TCMPT) is provided by this article. Additionally, this article describes a new classification of TCMPT, mechanism of action, clinical treatment, indications contraindications and adverse events reports.